2022
DOI: 10.1111/jgs.17726
|View full text |Cite
|
Sign up to set email alerts
|

Reasons for repeated emergency department visits among community‐dwelling older adults with dementia in Ontario, Canada

Abstract: Background: Community-dwelling older adults living with dementia visit the emergency department (ED) more frequently than other older adults, but research on the reasons for repeated visits is lacking. We examined the rate of repeated ED visits and reasons for visits in a cohort of individuals with dementia. Methods: We conducted a population-based retrospective cohort study of community-dwelling older adults (≥66 years) living with dementia in Ontario, Canada, who visited the ED and were discharged home betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 35 publications
0
22
0
Order By: Relevance
“…Without a standard strategy for cognitive screening in the ED, cognitive impairment in the absence of delirium would remain highly undetected, 3,5 as most patients identified as cognitively impaired in the 10‐CS did not have a previous dementia diagnosis or substantial cognitive complaints. Like delirium, cognitive impairment without delirium was associated with increased in‐hospital adverse events, prolonged LoS, and in‐hospital mortality, capturing risks beyond routine ED measures 1–3 . Although barriers exist (e.g., resource‐constrained settings and stressors related to acute illnesses), 9,10 our findings encourage broader cognitive screening for older patients in the ED.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Without a standard strategy for cognitive screening in the ED, cognitive impairment in the absence of delirium would remain highly undetected, 3,5 as most patients identified as cognitively impaired in the 10‐CS did not have a previous dementia diagnosis or substantial cognitive complaints. Like delirium, cognitive impairment without delirium was associated with increased in‐hospital adverse events, prolonged LoS, and in‐hospital mortality, capturing risks beyond routine ED measures 1–3 . Although barriers exist (e.g., resource‐constrained settings and stressors related to acute illnesses), 9,10 our findings encourage broader cognitive screening for older patients in the ED.…”
Section: Discussionmentioning
confidence: 69%
“…Patients with cognitive impairment, particularly those living with dementia, are more likely to be admitted to the hospital and die after an emergency department (ED) visit 1,2 . Nonetheless, cognitive assessments at the ED are scarce and primarily focused on delirium 3,4 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increase in the ascertainments in hospital is concordant with published reports that hospital admission rates for dementia and delirium increased or held study during the pandemic even as overall hospitalisation rates declined. 2 31–33 The population with 11 or more health conditions is small, representing approximately 7% of the older adult population without dementia, but is highly comorbid, is at high risk of developing dementia and frequently uses the healthcare system. 34 The higher incidence in this population may be partially a result of increased social isolation in those living alone and visitation restrictions in hospitals and congregate care settings.…”
Section: Discussionmentioning
confidence: 99%
“… 23 Other studies reported even higher rates possibly owing to their different focuses on populations with older age or affected by particular diseases, for instance, the rate was recorded as 60% among patients over 75 years 8 or was two-thirds (66.1%) among community-dwelling older adults living with dementia. 24 The exact reasons for high ED-return rates in older patients are uncertain, but may depend on potential factors such as poor quality of care or medical errors at the initial ED visit, patient’s chronic medical conditions with high relapse possibilities, and inadequate primary care or continuity of care.…”
Section: Discussionmentioning
confidence: 99%